Uniaxial tensile behaviour of additively manufactured elastically isotropic truss lattices made of 316L. (15th June 2022) - Somlo, K.; Chauhan, S.S.; Niordson, C.F.; Poulios, K.
Abstract: Metal additive manufacturing facilitates the production of complex light-weight structures, such as lattice structures, using a wide range of materials. In this work, elastically isotropic truss lattice structures are investigated, produced by laser powder bed fusion (LPBF) from austenitic 316L stainless steel. The lattice specimens are used to explore the effect of different unit cell sizes, orientations and volume fractions on the mechanical behaviour. Quasi-static, uni-axial tensile experiments are carried out with 3D digital image correlation (DIC) measurements. The experiments are validated by finite element (FE) simulations in order to unravel the governing mechanism of the tensile strength and deformation behaviour for the tested specimens. Comparisons are performed by means of force–displacement curves and strain distribution maps. For all lattice types, the geometrical deviations due to manufacturing are quantified and their impact on the mechanical properties is investigated using numerical models. The high resolution DIC measurements provide a detailed insight into the failure mechanisms of the specimens, which are also captured numerically for specific cases. The capabilities of experimental and computational methods are combined to reveal the uncertainties in the mechanical properties of LPBF produced truss lattice structures.